Now what? : a math tale - Harris, Robie H (Candlewick Press, 2019)
Solve a problem with Puppy and a bag full of blocks in this gentle introduction to early math concepts. Puppy wants to build a bed out of blocks, one that is wide enough and long enough for a snooze. But there aren't enough rectangles, squares, and triangles. NOW WHAT? Build, measure, count, compare! Follow along as Puppy tries again and again and again and finally figures out how blocks of different shapes and sizes can fit together to build a bed that's just the right size for a nap. -- adapted from publisher's website.